2023
DOI: 10.21203/rs.3.rs-2615729/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatio-temporal characteristics and influencing factors of air quality in Hunan Province: investigation based on functional data model

Abstract: With rapid economic growth and restriction by the adverse geographical and meteorological conditions, air quality control and improvement in Hunan Province are difficult. Based on the daily air quality data of Hunan Province from 2015 to 2019, in this paper, functional data analysis techniques (including principal component analysis, regression model, time series prediction model) were used to study the spatial-temporal characteristics, influencing factors, and future development trends of Air Pollution Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…With the development of geographic information system (GIS) and the wide application of multivariate statistical analysis, it is possible to carry out research from the national [9][10][11], provincial [12,13], special geographical areas [14][15][16] and other macro scales. Jiao Jinying et al (2022) quantified the factors affecting the spatial distribution of 2424 traditional villages in the Henan section of the Yellow River Basin, and found that natural factors such as rivers and topography were the main factors, followed by human factors [17]; Li J et al (2022) studied the spatial characteristics of 98 traditional villages along the Han silk road in Ningxia and found that the central settlements and transportation were the main influencing factors, and the influence of human factors was significantly greater than that of natural factors [18].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of geographic information system (GIS) and the wide application of multivariate statistical analysis, it is possible to carry out research from the national [9][10][11], provincial [12,13], special geographical areas [14][15][16] and other macro scales. Jiao Jinying et al (2022) quantified the factors affecting the spatial distribution of 2424 traditional villages in the Henan section of the Yellow River Basin, and found that natural factors such as rivers and topography were the main factors, followed by human factors [17]; Li J et al (2022) studied the spatial characteristics of 98 traditional villages along the Han silk road in Ningxia and found that the central settlements and transportation were the main influencing factors, and the influence of human factors was significantly greater than that of natural factors [18].…”
Section: Introductionmentioning
confidence: 99%